Immunogenicity to the bivalent HPV-16/18 vaccine among adolescent African students exposed to helminths and malaria - Miriam Nakalembe; Cecily Banura; Proscovia Bazanye Namujju; Florence Maureen Mirembe (Journal of Infection in Developing Countries)
Introduction: Efficacious vaccines that prevent human papillomavirus (HPV) infection, the recognized cause of cervical cancer, are now available. However, in sub-Saharan Africa, immune-modulating infections such as helminths and malaria may affect immunogenicity to the HPV vaccine. This study aimed to evaluate the effect of helminth infections and exposure to malaria on the immune response to the bivalent HPV-16/18 vaccine. Methodology:AS04-adjuvanted HPV-16/18 vaccinated students between 10 and 16 years of age from western Uganda, at 18 months-post vaccination were followed up for six months. After consent was obtained, demographic data, blood, and stool samples were collected. Multiplex HPV serology technology was used to determine HPV-16/18 antibody levels expressed as median fluorescent intensity (MFI). The malaria antibody immunoassay test was used to detect antibodies to malaria parasites. The Kato-Katz method was used to detect the presence of helminths. HPV-16/18 antibody levels among students exposed to malaria or helminths were compared with those who were not exposed using the Student’s t-test. Results: A total of 211 students participated in the study. There was no difference between MFI levels to HPV-16/18 antibodies at 18- and 24-month follow-ups among students who were positive and negative to malaria or helminth exposure. There was an increase in HPV-18 MFI antibody levels at month 24 among the students who were positive for malaria at enrolment (p = 0.05). Conclusions:Immune-modulating parasites (malaria/helminths) were not associated with reduced immune response to the bivalent HPV-16/18 vaccine. The data may support the use of this vaccine in sub-Saharan Africa.